Peran Orang Tua dalam Pengembangan Keterampilan Sosial-Emosional pada Anak - Aprilia Rianti Renada; Prilia Khoirunnisa; Satia Utami; Nuria Febriana; Vera Juwita; Desvi Wahyuni (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Human beings undergo a process of growth and development, which includes physical motor development, cognitive development, language development, artistic development, social-emotional development, and moral development. The early years are crucial for providing children with various perspectives on life and preparing them for their future. In the current crisis situation, it is essential to establish a foundation for emotional and social development. Research Problem and Aim: The study aims to provide a better understanding of the concrete role of parents in developing social and emotional skills in young children and how they can help children prepare for subsequent developmental phases more effectively. The role of parents is crucial in shaping and honing social-emotional skills, which are essential components of building emotionally and socially balanced individuals. Methodology This research adopts a literature study approach, gathering, evaluating, and synthesizing information from various sources such as scientific journals, books, articles, and publications related to the topic of the role of parents in the development of social-emotional skills in children. The study emphasizes the importance of social-emotional development in early childhood, as it significantly impacts a child's future life. Children with good social-emotional skills are better equipped to adapt to their environment and have a higher chance of success. Training emotional skills in young children is crucial to help them overcome negative emotions like anger and fear. Implications: The findings underscore the significance of social-emotional development in early childhood and the need for parents and educators to understand and support children in developing these skills. Parents can assist children in managing negative emotions and developing social skills, ultimately aiding them in regulating their emotions effectively.